Human Trafficking and Migrant Workers: Analysis of Indonesian Migrant Workers Protection in Overseas - Mahardika, Angga Putra; Wicaksono, Sonny Saptoajie (Law Research Review Quarterly, 2020)
The problems in this research are concerning to the regulations on the legal protection of illegal Indonesian migrant workers abroad who are victims of trafficking in persons already comprehensive, and the forms, mechanisms and procedures for legal protection of illegal Indonesian migrant workers abroad who are victims of trafficking in persons in BP3TKI Central Java already comprehensive?This thesis research uses a qualitative approach with a juridical-empirical method. The results of research and discussion show that based on Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers Overseas (PMI Law), the protection provided to victims of human criminal acts includes legal, social and economic protection. Whereas Law Number 21 of 2007 concerning Eradication of the Criminal Act of Trafficking in Persons (Huma Trafficking Act) grants the right to victims of human trafficking, among others, restitution, rehabilitation and repatriation. The most important form of legal protection for Indonesian migrant workers who are victims of trafficking in persons by Central Java BP3TKI is the repatriation of victims. In addition, the BP3TKI also conducts law enforcement against the perpetrators who are suspected of committing criminal acts of people. In conducting protection efforts, the Central Java BP3TKI collaborates with various parties such as the local police, BNP2TKI, and representatives of the Indonesian state in the placement country.